HUBUNGAN PETANI KARET DENGAN TAUKE (PATRON-CLIENT) DI DESA SUNGAI JALAU KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Anita, Sri; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the marketing channel and identify the pattern of the relationship between farmers and tauke in the Sungai Jalau village. This study executed in countryside of Sungai Jalau North Kampar at Kampar Regency. This study uses the survey method, sampling technique respondents conducted by purposive sampling. Number of samples 3 people tauke and 28 people rubber farmers. Analysis of the data was analyzed by descriptive qualitative. The result of the study shows that, marketing channels trought which farmers rubber consists of two channels. Rubber farmers Sungai Jalau sell ojol trader gatherer. The farmers can not sell ojol to the factory because small production and need big costs for sell to factory. The traders gatherer on channel 2 sell ojol to wholesalers because trader gatherer do not have permission sell ojol to the factory and to reduce of the cost. Trader getherer on channel 1 sell to the factory, because can get price higher than the wholesaler price. Relations between farmers and tauke in the Sungai Jalau village was patron - client relationship, dependence relationship, resiprosity relationship, loyalty relationship and personality relationship. The relationship of reciprocity; farmers helping tauke to raised ojol of storage (river) to the car to be weighed, after that tauke gived pay to farmer. Loyalty relationship, tauke and farmers, they helped an event without coercion. Personal relationship; relationship of mutual trust and solidarity between farmers and tauke. Keywords: Marketing, Patron â Client, Social Relations